MODERN CHALLENGES OF HIGHER EDUCATION' DEVELOPMENT IN LATVIA AND UKRAINE - Iryna Kalenyuk; Deniss Djakons (Izdevnieciba "Baltija Publishing", 2019)
The article is analyzed the tendencies and challenges of the development of higher education systems in Latvia and Ukraine. The determinative tendencies of the modern development of the world are globalization, digitalization, networking, virtualization, etc. Under these conditions, there is a colossal increase in the need for higher education. It has the following results: an increase in the number of students, the share of population coverage in higher education and, in general, people with higher education. The systems of higher education in Latvia and Ukraine are developing in line with world trends, increasing their scale and coverage of the population with higher education. The common features in the development of higher education in Latvia and Ukraine are revealed: the increase of the student contingent, the extension of the principles of lifelong learning, the exit of domestic higher education institutions into the international market of educational services, the enhancement of academic mobility and the growth of the number of foreign students. The active positions of both countries in the process of internationalization and the growth of academic mobility are confirmed. Equally important in the context of the research are the tendencies of increasing the number of researchers, increasing the number of patents, as well as increasing the level of interest of the business sector in the financing and implementation of product and process innovations.The main problems in the development of higher education of both countries are identified: insufficient amount of financing, insufficient diversification of sources of funding, poor presence of institutions of higher education in world university rankings, low level of financing of scientific research.